2009
DOI: 10.1186/1755-8794-2-46
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of acute multiple sclerosis relapses by transcription levels of peripheral blood cells

Abstract: BackgroundThe ability to predict the spatial frequency of relapses in multiple sclerosis (MS) would enable physicians to decide when to intervene more aggressively and to plan clinical trials more accurately.MethodsIn the current study our objective was to determine if subsets of genes can predict the time to the next acute relapse in patients with MS. Data-mining and predictive modeling tools were utilized to analyze a gene-expression dataset of 94 non-treated patients; 62 patients with definite MS and 32 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 55 publications
0
38
0
1
Order By: Relevance
“…Prediction of relapse using MRI loading, or factoring the number and location of lesions, is becoming more promising to diagnose exacerbations. 10 Signs and symptoms of MS depend on the area of CNS involvement and can result in a plethora of symptoms. Patients with MS have sensorimotor and balance impairments, ataxia, tremor, seizures, cranial motor impairments, cognitive deficits, and behavioral disorders.…”
mentioning
confidence: 99%
“…Prediction of relapse using MRI loading, or factoring the number and location of lesions, is becoming more promising to diagnose exacerbations. 10 Signs and symptoms of MS depend on the area of CNS involvement and can result in a plethora of symptoms. Patients with MS have sensorimotor and balance impairments, ataxia, tremor, seizures, cranial motor impairments, cognitive deficits, and behavioral disorders.…”
mentioning
confidence: 99%
“…We replicated their findings that BCL2 is decreased and BNIP3 is increased. More recent work from the same group reports that expression of a small set of mRNA can be used to predict relapse (14), but the transcripts they used as predictors were not altered in our patients. Arthur et al also reported a comparison of unpaired relapse and remission patients (6), but comparison with their results is difficult since they compared relapse to controls and remission to controls rather than directly comparing relapse and remission.…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…Dendrogram constructed using BRB ArrayTools with centered correlation and average linkage. The branch labels give the experiment number (1)(2)(3)(4)(5), the subject number (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), clinical status, treatment, and gender. The samples from the first two experiments formed large clusters.…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…le taux d'erreur du deuxième niveau était 2,3 fois plus faible que celui de prédictions aléatoires (taux d'erreur = 0,35, p < 0,001). 106 …”
Section: Profil De L'expression Génétiqueunclassified